2007
DOI: 10.1899/06-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic macroinvertebrate response along a gradient of lateral connectivity in river floodplain channels

Abstract: Large river floodplains potentially include the full range of freshwater ecosystems from permanently flowing channels to temporary pools and springs. Attempts to restore such complex systems require tools adapted to assess restoration success. In an analysis of invertebrate assemblages in the Rhoˆne River floodplain (France), taxonomic-based indices (rarefied richness and assemblage composition) were compared with functional metrics using trait-based ratios as surrogates of ecosystem processes. Their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 46 publications
4
80
0
2
Order By: Relevance
“…The paleochannel in the current study therefore reflects the evolution of one channel section with a period of active flow and a second representing isolation and eventual terrestrialisation. The temporal pattern reflected in the sequences is characteristic of the spatial pattern recorded on contemporary floodplain water bodies (Castella et al 1984;Paillex et al 2007), where active channels, cut-offs and isolated backwaters may all exist in close proximity, and highlights the biological value of diverse floodplain water bodies, and paleochannels in the study of river channel evolution.…”
Section: Trichoptera Fauna From Life Flow Groups I and Ii (Glossosomamentioning
confidence: 88%
“…The paleochannel in the current study therefore reflects the evolution of one channel section with a period of active flow and a second representing isolation and eventual terrestrialisation. The temporal pattern reflected in the sequences is characteristic of the spatial pattern recorded on contemporary floodplain water bodies (Castella et al 1984;Paillex et al 2007), where active channels, cut-offs and isolated backwaters may all exist in close proximity, and highlights the biological value of diverse floodplain water bodies, and paleochannels in the study of river channel evolution.…”
Section: Trichoptera Fauna From Life Flow Groups I and Ii (Glossosomamentioning
confidence: 88%
“…Table 2). Previous research (Paillex et al, 2007;Gallardo et al, 2008) showed that diversity and abundance of macroinvertebrates would increase with the increase of hydrological connectivity. In the river-disconnected lakes, macroinvertebrate assemblages in the lakes at low level of eutrophication were characterized by dominance of epiphytic animals, and those in other lakes at high level of eutrophication were characterized by dominance of pollution-tolerant animals (Pan et al, 2012).…”
Section: Macroinvertebratesmentioning
confidence: 97%
“…Although these sites have all a permanent connection, the influence of the main river can still vary. These variations in connection with the main channel have been quantified by a synthetic index of lateral connectivity that includes several site characteristics (Paillex et al, 2007). In the rest of the paper, we refer to this index as lateral connectivity.…”
Section: Characterization Of Study Site Typesmentioning
confidence: 99%
“…Mixture of HNO 3 and H 2 O 2 (4:1 v/v) (Suprapur reagents, Merck, Darmstadt, Germany) was added to the biological material and left overnight. The digestion was performed at 80°C during 1 h. Table 1 The four site types with their locations and connectivity index (CI), calculated as in (Paillex et al, 2007), 0 meaning no lateral connection to the river, and 1 full permanent connection with the river.…”
Section: Sample Preparation and Digestionmentioning
confidence: 99%
See 1 more Smart Citation